Klasifikasi Lonjakan Ekstrem Nilai Tukar USD/IDR Menggunakan Gaussian Naïve Bayes - Meini Syakinah Ritonga; Rita Novita Sari (LKP Unity Academy, 2025)
The fluctuation of the Rupiah exchange rate against the US Dollar (USD/IDR) potentially triggers macroeconomic instability. This study aims to classify potential extreme surges in the USD/IDR exchange rate using data mining techniques with the Gaussian Naïve Bayes algorithm. A total of 502 daily historical observation data were extracted into four continuous predictor features: volatility, closing difference, upper bound difference, and lower bound difference. The evaluation was conducted using an 80% training and 20% testing data split. The results show that the model can identify